Association of COMT and SLC6A3 polymorphisms with impulsivity, response inhibition and brain function. (October 2015) - Kasparbauer, Anna-Maria; Merten, Natascha; Aichert, Désirée S.; Wöstmann, Nicola; Meindl, Thomas; Rujescu, Dan; Ettinger, Ulrich
Abstract: Evidence of the genetic correlates of inhibitory control is scant. Two previously studied dopamine-related polymorphisms, COMT rs4680 and the SLC6A3 3′ UTR 40-base-pair VNTR (rs28363170), have been associated with response inhibition, however with inconsistent findings. Here, we investigated the influence of these two polymorphisms in a large healthy adult sample ( N  = 515) on a response inhibition battery including the antisaccade, stop-signal, go/no-go and Stroop tasks as well as a psychometric measure of impulsivity (Barratt Impulsiveness Scale) (Experiment 1). Additionally, a subsample ( N  = 144) was studied while performing the go/no-go, stop-signal and antisaccade tasks in 3T fMRI (Experiment 2). In Experiment 1, we did not find any significant associations of COMT or SLC6A3 with inhibitory performance or impulsivity. In Experiment 2, no association of COMT with BOLD was found. However, there were consistent main effects of SLC6A3 genotype in all inhibitory contrasts: Homozygosity of the 10R allele was associated with greater fronto–striatal BOLD response than genotypes with at least one 9R allele. These findings are consistent with meta-analyses showing that the 10R allele is associated with reduced striatal dopamine transporter expression, which in animal studies has been found to lead to increased extracellular dopamine levels. Our study thus supports the involvement of striatal dopamine in the neural mechanisms of cognitive control, in particular response inhibition.